ORGANIZATION OF GASTRONOMIC TOURISM IN UZBEKISTAN - Jalilov Shokhjakhon Kholbozor ogli (European Science Publishing, 2025)
The article highlights the fact that gastronomic tourism is one of the fields of tourism that has been coming to our country since recent years, and today the importance of gastronomy tourism in our republic, the development of Uzbek national traditions, customs, national dishes and world standards.
Keywords: Gastronomy, gastronomic tourism, gastronomic tourist, national dishes, tourism industry, World Tourism Organization (UNWTO), gross domestic product (GDP), wine(eno)-tourism.